2017
DOI: 10.1016/j.jallcom.2016.08.117
|View full text |Cite
|
Sign up to set email alerts
|

Energy filtering enhancement of thermoelectric performance of nanocrystalline Cr1− Si composites

Abstract: We report on thermoelectric properties of nanocrystalline Cr1−xSix composite films. As-deposited amorphous films were transformed into a nanocrystalline state with average grain size of 10-20 nm by annealing during in-situ thermopower and electrical resistivity measurements. The partially crystallized films, i.e. the films consisting of crystalline grains dispersed in the amorphous matrix, are a new type of the heterogeneous material where the nanocrystalline phase plays the role of scattering centers giving r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…According to the calculation results, [115] low-energy carriers negatively contribute to S (Figure 7c), while the carriers that have higher energy between www.advancedsciencenews.com 0.05 and 0.1 eV contribute the most for high S. [115] By introducing potential barriers between grain boundaries, lowerenergy or minor charge carriers can be filtered, [213] and the average carrier energy can be increased. [205,207,214] The calculation results estimate significant improvement on S 2 σ when well-designed potential barriers were introduced, [205] while many experimental results confined that applying energy filters can effectively enhance the TE performance. [205,207,214] The calculation results estimate significant improvement on S 2 σ when well-designed potential barriers were introduced, [205] while many experimental results confined that applying energy filters can effectively enhance the TE performance.…”
Section: Energy Filteringmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the calculation results, [115] low-energy carriers negatively contribute to S (Figure 7c), while the carriers that have higher energy between www.advancedsciencenews.com 0.05 and 0.1 eV contribute the most for high S. [115] By introducing potential barriers between grain boundaries, lowerenergy or minor charge carriers can be filtered, [213] and the average carrier energy can be increased. [205,207,214] The calculation results estimate significant improvement on S 2 σ when well-designed potential barriers were introduced, [205] while many experimental results confined that applying energy filters can effectively enhance the TE performance. [205,207,214] The calculation results estimate significant improvement on S 2 σ when well-designed potential barriers were introduced, [205] while many experimental results confined that applying energy filters can effectively enhance the TE performance.…”
Section: Energy Filteringmentioning
confidence: 96%
“…As a consequence, S can be increased while σ will not be significantly reduced. [28,214] Figure 7d shows an example of the enhanced S 2 σ via energy filtering by manipulating grain boundaries [28] of Yb-filled CoSb 3 compared with its counterparts [215] without energy filters. [28,214] Figure 7d shows an example of the enhanced S 2 σ via energy filtering by manipulating grain boundaries [28] of Yb-filled CoSb 3 compared with its counterparts [215] without energy filters.…”
Section: Energy Filteringmentioning
confidence: 99%
“…При этой температуре происходит изменение наклона зависимостей термоэдс и электрического сопротивления от температуры. При этом, согласно данным рентгеноструктурного анализа, пленка остается аморфной [3]. Это указывает на то, что аномалии в температурных зависимостях термоэдс и электрического сопротивления связаны с изменением ближнего порядка в аморфной структуре.…”
Section: экспериментальные результаты и обсуждениеunclassified
“…Это, как правило, приводит к заметному уменьшению решеточной теплопроводности за счет рассеяния фононов на границах кристаллитов. Недавно мы показали, что в нанокристаллических пленках силицидов хрома и марганца, полученных путем кристаллизации из аморфного состояния, повышается термоэлектрический фактор мощности PF = S 2 /ρ [2,3]. Это повышение связано с ростом термоэдс в сильно легированных полупроводниках за счет селективного рассеяния носителей заряда на границах нанокристаллов.…”
Section: Introductionunclassified
“…, where is Seebeck coefficient, is electrical conductivity and is thermal conductivity [1]. Resent progress in increasing ZT has been mainly driven by a reduction of thermal conductivity via nanostructuring approach [6][7][8][9][10][11][12][13][14]. It has been demonstrated that thermal and electrical transport is influenced by crystallite boundary scattering.…”
mentioning
confidence: 99%